Modelos vivos em uso: Poesia e performance de Ricardo Aleixo (em) um exercício crítico de literatura contemporânea - Santos, Luciany Aparecida Alves (2015)
This doctoral thesis in partnership with Ricardo Aleixo’s book, Modelos vivos (2010) presents a critical exercise of experimentation of Contemporary Literature. In this work, Criticism and Literature are considered concurrently. In dialogue with Theories of Literature, Theories of Performance, Yorubá Cosmology, Philosophy and Biology Studies, we have constituted a work with contemporary poet Ricardo Aleixo’s performance and poetry. In this study the Modelos vivos’ book is presented in use, that is, it is experienced as an object. This thesis is illustrate with pictures by Ricardo L.A.F. and Antonio Dupeixe’s designs and paintings. Therefore, in use with Modelos vivos, this thesis studies Ricardo Aleixo’s performance and poetry, Criticism and Contemporary Literature.